Sustainable Development – the Key to Competitiveness CSR as an added value to Alstom’s corporate performance - Sreeganthan, Priya (My University, 2015)
Corporate social responsibility or CSR is today a widely recognized concept which is receiving in- creasing popularity extremely rapidly, especially in the business world. The pressure on companies to carry out their business practices in ethical manners, which promote the wellbeing of the environment and society, is coming from all directions and all stakeholders. Alstom, a French multinational conglomerate operating in the rail transport and energy industry, is no exception to this norm. This company, which will be used as the case example in this thesis, is being brought to bay in terms of engaging in CSR practices and practicing business with high ethics. It is surely not a negatively conceived phenomenon that CSR is being put on a pedestal – quite the opposite. Instead of corporations practicing CSR only to meet their stakeholder requirements through practicing window dressing, many corporations actually strive to benefit from the practice of corporate social business. In addition to bringing benefit to externals a corporation such as Alstom itself can benefit from being involved in CSR. The purpose of this thesis is to evaluate the current strategic values and the future perspectives of CSR at Alstom and moreover the added value which the practice of CSR could bring Alstom as a business. A set of perspectives from a futures studies viewpoint is looked at, with critical examination of the company’s current corporate practices as well as the CSR related studies and theories written for corporations. Through this, some solutions and practices will be suggested to Alstom in order for it to fully utilize the potential of corporate social business and the value it can bring in the most probable futures that the company is expected to face. By utilizing the Soft Systems Methodology (SSM), a method mainly used in organizations to solve problematic issues in management and policy contexts, a process is developed to see what improvements could be of help in improving Alstom and its way towards involving CSR in its business practices even more than it currently does. Alstom is already deeply involved in the practicing of CSR and its vision has a strong emphasis on this popular concept of today. In order to stay in the game and to use CSR as a competitive advantage to the company, Alstom ought to embed corporate social practices even deeper in its organizational culture by using them as a tool to reduce risk and costs, increasing employee commitment and customer loyalty and to attract socially responsible investors, just to name a few. CSR as a concept is seen to have great potential in the future, an opportunity Alstom will not miss.